2014
DOI: 10.11138/ccmbm/2014.11.1.031
|View full text |Cite
|
Sign up to set email alerts
|

The role of the orthopaedic surgeon in the prevention of refracture in patients treated surgically for fragility hip and vertebral fracture

Abstract: SummaryThe role of the orthopaedic surgeon in the treatment of patients with fragility fractures is twofold: the conservative or surgical treatment of the fracture, and the prevention of further fractures, establishing diagnostic and therapeutic procedures for osteoporosis. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Multiple studies in different countries with variable results reported the importance of treating osteoporosis and its association with reducing hip refracture rate and mortality [12,13,14]. However, local data on this topic are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies in different countries with variable results reported the importance of treating osteoporosis and its association with reducing hip refracture rate and mortality [12,13,14]. However, local data on this topic are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[34] A recent study reported that an osteoporotic fracture represented the most important predictive factor for further osteoporotic fractures, so, every country in the world has been attempting to treat osteoporosis for the prevention of osteoporotic fractures and refractures. [56]…”
Section: Introductionmentioning
confidence: 99%
“…As the initially cartilaginous soft callus calcifies into a fracture‐stabilizing bony callus, osteoclasts return, and alongside osteoblasts, remodel the callus until physiological bone architecture is restored. Should fracture healing proceed inefficiently, however, the discontinuity caused by the fracture may persist or, following apparent healing, there may be persistent structural weakness that can contribute to re‐fracture . This is of concern in aged individuals, where the efficiency of the bone healing process is diminished.…”
mentioning
confidence: 99%
“…Should fracture healing proceed inefficiently, however, the discontinuity caused by the fracture may persist or, following apparent healing, there may be persistent structural weakness that can contribute to re-fracture. 4,5 This is of concern in aged individuals, where the efficiency of the bone healing process is diminished. Current strategies to improve skeletal healing include local surgical delivery of osteo-inductive materials or proteins and systemic delivery of anti-resorptive or anabolic therapy.…”
mentioning
confidence: 99%